Analisis Yuridis Putusan Nomor 18/G/2025/PTUN.MDN dalam Memutus Sengketa Pemberhentian Tidak Dengan Hormat Anggota Kepolisian Perspektif Siyāsah Qaḍā’iyyah - Hasibuan, Tika Agyuni Br; Zahara, Fatimah (AL-SULTHANIYAH, 2026)
Dispute of dishonorable discharge of police members, with a study on Decision Number 18/G/2025/PTUN.MDN, The main focus of this research is where the plaintiff objects to the procedure and substance of his dismissal. This research aims to determine the legal considerations of the Medan PTUN panel of judges in deciding the PTDH dispute of police members in decision number 18/G/2025/PTUN.MDN from the perspective of siyāsah qaḍā’iyyah. The research method used is normative legal research with a statutory approach and a conceptual approach. Data were obtained through a literature study of relevant laws and regulations and fiqh siyāsah literature. The Medan PTUN decision in this case still raises legal debate because it does not consider the procedural and substantial aspects of the dismissal of Polri members. This research contributes to improving the practice of administrative justice in Indonesia, especially in Polri personnel disputes